2015
DOI: 10.1515/ijamh-2015-5007
|View full text |Cite
|
Sign up to set email alerts
|

Attention-deficit hyperactivity disorder (ADHD), substance use disorders, and criminality: a difficult problem with complex solutions

Abstract: The association between attention-deficit hyperactivity disorder (ADHD) and criminality has been increasingly recognized as an important societal concern. Studies conducted in different settings have revealed high rates of ADHD among adolescent offenders. The risk for criminal behavior among individuals with ADHD is increased when there is psychiatric comorbidity, particularly conduct disorder and substance use disorder. In the present report, it is aimed to systematically review the literature on the epidemio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 163 publications
(203 reference statements)
2
31
0
Order By: Relevance
“…This is consistent with research that highlight selected environmental factors relevant in ADHD [17][18][19], argue for a better understanding of the environment factors that influence functional outcomes in ADHD [50,51], and promote interventions that help individuals with ADHD to more optimally perform in key environmental contexts [52], such as education [53], vocation [54], and community participation [9].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This is consistent with research that highlight selected environmental factors relevant in ADHD [17][18][19], argue for a better understanding of the environment factors that influence functional outcomes in ADHD [50,51], and promote interventions that help individuals with ADHD to more optimally perform in key environmental contexts [52], such as education [53], vocation [54], and community participation [9].…”
Section: Discussionsupporting
confidence: 73%
“…ADHD is associated with challenges to functioning in daily life, including academic and vocational difficulties [6,7], social exclusion [8], and delinquency [9,10]. Co-exiting psychiatric issues are also common [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…ADHD is a major public health problem as it is associated with impaired child and family functioning and high societal costs and often leads to academic underachievement, behavior problems, parent–child conflicts, and peer relationship difficulties (Barkley, Anastopoulos, Guevremont, & Fletcher, 1992; Bernfort, Nordfeldt, & Persson, 2008; Efron et al, 2014; Loe & Feldman, 2007; Marton, Wiener, Rogers, & Moore, 2015). ADHD is considered a chronic disorder and, when it is not diagnosed and treated early on, it may result in various negative developmental outcomes (e.g., occupational problems, other psychiatric disorders, substance abuse, criminal activity) across the life span as well as an increased rate of mortality (Cherkasova, Sulla, Dalena, Pondé, & Hechtman, 2013; Dalsgaard, Østergaard, Leckman, Mortensen, & Pedersen, 2015; Knecht, De Alvaro, Martinez-Raga, & Balanza-Martinez, 2015; Kooij et al, 2012; Kuriyan et al, 2013). …”
mentioning
confidence: 99%
“…After review, 49 articles were included based on their significance to ADHD and its association with alcohol abuse. Table 1 lists various studies indicating an interdependence between the risk of alcohol use and ADHD patients [4,8,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Several studies have reported that ADHD and alcohol abuse have a direct positive correlation [30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Reviewmentioning
confidence: 99%
“…Even though there are multiple contradictory reports, those in favor of the higher risk of alcohol abuse in ADHD adolescents were found to be greater. Furthermore, an association has also been indicated between alcohol and substance abuse and the risk of criminal behavior in ADHD [15]. Due to the lack of recovery of motor control [47] in patients suffering from ADHD as compared to non-ADHD, the risk of driving under alcohol influence also increases [48].…”
Section: Adhd Does Not Lead To Alcohol Abusementioning
confidence: 99%